Serum MyomiRs as Biomarkers for Female Carriers of Duchenne/Becker Muscular Dystrophy - Zhang, Jiapeng; Meng, Qi; Zhong, Jingzi; Zhang, Min; Qin, Xiao; Ni, Xiaohua; Ma, Jiawen; He, Yangwen; Zeng, Dan; Lan, Dan (Frontiers in Neurology, 2020)
Background: Duchenne/Becker muscular dystrophy (DMD/BMD) is an X-linked recessive lethal neuromuscular disease. MicroRNAs expressed in striated muscle, myomiRs, have been proposed as its potential biomarkers. Serum creatine kinase (CK) is commonly used as a biomarker in clinical practice, but it is not reliable. The aim of this study was to assess whether serum levels of myomiRs has diagnostic value for detection of female DMD/BMD carriers with normal or elevated CK. Methods: Thirty four female carriers and 33 age-matched healthy female controls were enrolled. Peripheral blood samples were collected and serum miRNAs were extracted for measurement of miR-1, miR-133a, miR-133b, miR-206, miR-208a, miR-208b, and miR-499 by quantitative real-time polymerase chain reaction. Results: MiR-1, miR-133a, miR-133b, miR-206, miR-208a, miR-208b, and miR-499 were upregulated in all female carriers in comparison to healthy controls. MiR-1 (Spearman's rho = +0.406, p = 0.017) was correlated with CK in the female carrier group. Receiver operating characteristic curve analysis of all seven myomiRs showed that the area under the curve (AUC) for miR-499, miR-133b, miR-1, miR-208b, and miR-133a exceeded 70.0%, and for miR-206 and miR-208a exceeded 60.0%. MiR-133b and miR-499 were significantly increased in all female carriers, even those with normal CK. AUC for the combination of all seven miRNAs was 87.2%. CK (OR 0.406, 95% CI 0.000–0.001, p < 0.0001) and miR-499 (OR 0.323, 95% CI 0.023–0.106, p = 0.003) were considered to be independent predictors for female carriers presence in the multivariable regression analysis model. Conclusions: MiR-133b and miR-499 are potentially useful biomarkers for female carriers with DMD/BMD (including those with normal CK). The combination of all seven serum miRNAs and their respective combinations with CK have better diagnostic value for female carriers than either CK or any separate miRNA.